Property and reactivity of polyselenides and polysulfides: a quantum chemistry study. (4th May 2023) - Pi, Hui-Chu; Hu, Ching-Han
Abstract : High-level ab initio and density functional theory were applied to investigate property and reactivity of polyselenides and polysulfides. With CH3 Xn H (X = S or Se) we found that the deprotonation energy (and p Ka ) of CH3 Sen H, ionization potential (IP) of, and CH3 Sen −H bond dissociation energy (BDE) are lower than those of their sulfur counterparts. For n  = 2, IPs and X−H BDEs are exceptionally small. The relative nucleophilicity of C H 3 X n − vary with substrates. However, CH3 Sen H are more nucleophilic than CH3 Sn H due to their due to their lower deprotonation energy. The nucleophilicity of selenolates versus thiolates are related to the chemical nature. Selenium is more electrophilic than sulfur. GRAPHICAL ABSTRACT: UF0001